2018
DOI: 10.1002/cssc.201801908
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Fullerene Organic Electron‐Transporting Materials for Perovskite Solar Cells

Abstract: What prompted you to investigate this topic/problem? Organice lectron transporting materials (ETMs) are very attractive for perovskite solar cells (PSCs) due to their high electrontransporting properties and solution processability.T oo vercome disadvantage of widely used fullerene-based organic ETMs, recently non-fullerene-based organic ETMs were developed for high-performance (efficiency and stability) PSCs. Our Conceptd escribes recently developed non-fullereneo rganic ETMs for normala nd inverted-structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…ETLs, generally possessing electron rich centers such as sulfur and nitrogen, can act as Lewis base and the passivation of electron‐trap centers could be replaced by the coordination of N‐Pb and S‐Pb. Therefore, ETLs with optimized passivation groups should get rid of nonradiative recombination and mitigate hysteresis . As shown in Figure , some trials have been demonstrated to passivate these defects through the introduction of thiophene and pyridine groups .…”
Section: Introductionmentioning
confidence: 99%
“…ETLs, generally possessing electron rich centers such as sulfur and nitrogen, can act as Lewis base and the passivation of electron‐trap centers could be replaced by the coordination of N‐Pb and S‐Pb. Therefore, ETLs with optimized passivation groups should get rid of nonradiative recombination and mitigate hysteresis . As shown in Figure , some trials have been demonstrated to passivate these defects through the introduction of thiophene and pyridine groups .…”
Section: Introductionmentioning
confidence: 99%
“…There has been vast research focusing on exploring novel HTL materials. As the counterpart, the progress on ETL materials is slower. To ensure that n-type materials have better performance in PSCs, they should have good solubility, high electron mobility, and suitable energy levels aligned with perovskite materials . Currently, most of the present electron-transport materials are based on n-type organic semiconductors, especially those with large planar π-conjugated structures.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, non-fullerene acceptors in organic solar cells (OSCs) constructed from indaceno­dithiophene (IDT), indaceno­dithieno­[3,2- b ]­thiophene (IDTT), and their analogues have attracted wide attention due to their tunable energy levels and good charge transport, resulting from the rigid multifused ring. With these intrinsic advantages, they were also utilized as ETL materials for PSCs, and excellent PCE results up to 19% were obtained, which encouraged researchers to discover more novel efficient ETL materials. , …”
Section: Introductionmentioning
confidence: 99%
“…In inverted p-i-n architecture, fullerene and corresponding derivatives have been used as the most common ETL materials. However, the temporal stability of fullerene and corresponding derivatives is also poor, which can be evident from the morphological changes upon recrystallization [214]. Therefore, the research about ETL is still in a beginning stage, especially for the non-fullerene ETL.…”
Section: Polymers In Perovskite Solar Cellsmentioning
confidence: 99%